Keadilan Gender dalam Al-Qur’an: Perspektif Nashr Hamid Abu Zayd terhadap Analisis Ayat-Ayat Poligami - Fitratuddiniy , Indah Dianis Asriy; Jamila, Winni Sabron; Jamil, Ru’yatul Ainil (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2025)
This research explores the theme of gender justice in the Qur'an by focusing on Nashr Hamid Abu Zayd's perspective on the analysis of polygamy verses. In this context, the research utilises the literature review method to investigate Abu Zayd's views on the fair treatment of wives in polygamous practices. The article details Abu Zayd's arguments and interpretations, highlighting the controversial aspects of understanding the verses. By approaching this topic through the library research method, this study aims to contribute to the literature that explores the concept of gender justice in Islam. The results are expected to open a space for dialogue and a deeper understanding of gender roles in Qur'anic interpretation, especially in the context of the dynamics of modern society. This research also emphasizes the importance of contextualizing Quranic verses on polygamy within modern social realities. It advocates for interpretations that prioritize justice, equity, and the dignity of all parties involved. Such an approach fosters a more balanced understanding that aligns with contemporary values while respecting traditional teachings. Ultimately, this study supports progressive dialogue and reinterpretation in Islamic gender discussions, promoting harmony and fairness in marital relationships.